Analysis And Measurement Of Bfu520w Lna Design For Vhf Application - Manogaran, Saravanan (2014)

(untitled)
The Low Noise Amplifier (LNA) is one of the critical blocks in a receiver chain lineup of a two way portable radio. The main function of a LNA is to amplify weak signals without adding excessive noise. LNA design optimization in the conventional way often involves tedious and iterative process that takes various parameters trade-off into considerations such as gain versus Third-order Intercept Point (IIP3), Noise Figure (NF), 1dB compression point and F2 Blocking. Choosing the best possible LNA design has always been a daunting task for designers across the globe. This research identifies the BFU520W as one of the LNA which meets the important criteria in the portable two way radio communication world. This validation proves that this LNA selection is a robust, efficient and yet comparable or better compared to legacy LNA topology. This LNA which is wideband capable needs to provide constant gain, low noise and unconditionally stable to ensure the whole receiver lineup, from the Front End till Back End meets the standard specification. In order to achieve this, BFU520W was validated to replace the legacy LNA as due cost constraints which will eventually reduce to 70% of its operating cost.The BFU520W was highlighted due to this reason and the performance are validated to be or as comparable as the legacy LNA,The susbsection results will be discussed at the end of this research and BFU520W is definitely the best ironic replacement for the Legacy LNA.